AN INTEGRATED DAY CARE MODEL IN URBAN CITY - Purnomo, Erwin; Kanamutya, Kanamutya; Mulyo, Lucky; Imam, Karen Peyronnin (Journal of Business Strategy and Execution, 2013)
The Economic growth has become one of factors that influenced the change of lifestyle and social improvement in Indonesia. As people buying power increase, they tend to shift their purchase preference and consumption to better services and products. Lately, it was happened a phenomenon, where day care becomes the most talked-about topic among working employee who has young kids. Means that, day care now is being reconsidered as part of alternative for people in take care of their child rather than using Babysitter. It showed significantly progress of good market recognition from people related to this day care existence, specifically for group based day care that already exists in Jakarta. Although most people still compare day care to babysitting and make judgment that both of these services are similar even they perceive that babysitters are worthier, since group day care is just half day service, the enthusiasm to this kind of business still remain and began to bloom lately. The field condition shows such a big demand that every enrollment of one the biggest group based day care always reach their capacity that makes them put on waiting list. Therefore, through this research, we want to collect information about what exactly happened in Jakarta specifically related to day care trend among working people. This study is important for everyone who planned to establish similar business as well as become our preliminary study to recognize day care market for the business model that we will develop later. As market condition already mapped well, it’s easy to set proper segmentation, target, and positioning for our business model.